Domain Wall Motion Across Various Grain Boundaries in Ferroelectric Thin Films. Issue 6 (21st March 2015) - Marincel, Daniel M.; Zhang, Huairuo; Jesse, Stephen; Belianinov, Alex; Okatan, Mahmut B.; Kalinin, Sergei V.; Rainforth, W. Mark; Reaney, Ian M.; Randall, Clive A.; Trolier‐McKinstry, Susan; Damjanovic, D.
<x xml:space="preserve">Abstract</x> Domain wall movement at and near engineered 10°, 15°, and 24° tilt and 10° and 30° twist grain boundaries was measured by band excitation piezoresponse force microscopy for Pb(Zr, Ti)O3 films with Zr/Ti ratio of 45/55 and 52/48. A minimum in nonlinear response was observed at the grain boundary for the highest angle twist and tilt grain boundaries, while a maximum in nonlinear response was observed at the 10° tilt grain boundaries. The observed nonlinear response was correlated with the domain configurations imaged in cross section by transmission electron microscopy.